2021
DOI: 10.3390/ijerph18031300
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Intervention Studies Aiming at Reducing Inequality in Dental Caries among Children

Abstract: (1) Background: The objective is to systematically review the evidence on intervention programs aiming at reducing inequality in dental caries among children. (2) Methods: Two independent investigators searched MEDLINE, Cochrane library, and Ovid up to December 2020 to identify intervention studies assessing the impact on socioeconomic inequalities in dental caries among children. The interventions included any health promotion/preventive intervention aiming at reducing caries among children across different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 40 publications
(115 reference statements)
2
19
0
3
Order By: Relevance
“…In some cases, such as childhood caries, general population interventions (water fluoridation, etc.) have been shown to be more successful than population-specific and individual interventions [ 39 ]. TikTok videos could thus contribute to this reduction in inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, such as childhood caries, general population interventions (water fluoridation, etc.) have been shown to be more successful than population-specific and individual interventions [ 39 ]. TikTok videos could thus contribute to this reduction in inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…106 A recent systematic review of caries preventive interventions on children found limited evidence on reducing oral health inequalities. 107 For dental health education (a downstream intervention), the findings were equivocal, while the evidence was more conclusive about topical fluorides and water fluoridation reducing inequalities in childhood caries.…”
Section: Time For Ac Ti On To Addre Ss or He Ineq Ualitie Smentioning
confidence: 99%
“…To date, research on oral health promotion has concerned primarily preventive interventions [ 10 , 11 ], capacity development [ 12 , 13 ] and settings and policy approaches [ 14 ]. There are few published studies exploring dental professionals’ perspectives on health promotion and they are quantitative studies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%